A case of cholestasis caused by inferior vena cava filter. (29th July 2022) - Kuraoka, Naosuke; Ujihara, Tetsuro; Hashimoto, Satoru
Abstract : Cholestasis and obstructive jaundice can be caused by several factors. Kuraoka et al. report an extremely rare case of cholestasis due to occlusion of the distal bile duct by an inferior vena cava filter, which was confirmed on imaging. Jaundice improved after placement of a biliary stent.